Transepidermal water loss, stratum corneum hydration, and skin surface pH of female African and Caucasian nursing students. Issue 1 (20th July 2018) - Young, Monica M; Franken, Anja; du Plessis, Johan L
Abstract: Background: Conflicting evidence exists on how skin barrier function compares between Africans and Caucasians. This study measured skin barrier function of South African first year nursing students before their practical training started to compare skin barrier function between the racial groups. Methods: Transepidermal water loss (TEWL), stratum corneum (SC) hydration, and skin surface (SS) pH was measured on female first year nursing students (19 African and 31 Caucasian; age range 18‐40 years). Geometric means and ranges were calculated and the influence of anatomical areas and racial differences were evaluated respectively. Results: No significant difference in TEWL was established between the racial groups. SC hydration was significantly lower ( P  ≤ 0.05) and SS‐pH was significantly higher ( P  ≤ 0.0001) in African nursing students when compared to Caucasians. African nursing students had significantly lower ( P  ≤ 0.05) SC hydration on their palms when compared to the other anatomical areas. Conclusion: Stratum corneum hydration and SS‐pH differed significantly between African and Caucasian skin, while no difference was found for TEWL, the primary parameter used to evaluate skin barrier function. Low SC hydration and high SS‐pH of African nursing students prior to their practical training, may suggest a higher risk for developing occupational skin diseases.